Electromagnetic fields and heavy-ion orbiting in a low-temperature plasma with a magnetic pumping - Shamrai, K.P.; Kudriavchenko, E.N. (Вопросы атомной науки и техники, 2008)
The excitation of LF electromagnetic fields by various antennas in a magnetized plasma with a minor fraction of heavy ions is computed. The efficiency of heavy-ion acceleration owing to the parametric resonance in the ICR frequency range is examined. The effect of heavy-ion collisions with lighter ions and atoms is estimated. Розраховано збудження НЧ- електромагнітних полів різними антенами в плазмі з малою добавкою важких іонів. Досліджено ефективність прискорення важких іонів внаслідок параметричного резонансу в ІЦР діапазоні частот. Оцінено ефект зіткнень важких іонів з легкішими іонами та атомами. Рассчитано возбуждение НЧ- электромагнитных полей различными антеннами в плазме с малой добавкой тяжелых ионов. Исследована эффективность ускорения тяжелых ионов вследствие параметрического резонанса в ИЦР диапазоне частот. Оценен эффект столкновений тяжелых ионов с более легкими ионами и атомами.